2020
DOI: 10.1007/s42452-020-03492-6
|View full text |Cite
|
Sign up to set email alerts
|

Effect of sandblasting on the surface roughness and residual stress of 3Y-TZP (zirconia)

Abstract: A defined surface roughness is important for the adhesive bonding of veneering ceramic to zirconia frameworks. Thus, we investigated the effects that sandblasting has upon the surface roughness and residual stress of zirconia. So as to achieve well-defined blasting parameters and also generate highly reproducible results; a custom-made, automated sandblasting machine was constructed (based on a 3D-printer construction kit). Thirty-two samples (measuring 30 mm × 35 mm × 0.2 mm) were cut from densely sintered 3Y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(7 citation statements)
references
References 30 publications
1
5
0
1
Order By: Relevance
“…This suggests a chemical link between the veneering materials and the Y-TZP substrates, which strengthens the binding. Several other studies suggested that increasing the surface roughness of zirconia by using air abrasion increased ceramic bond strength by promoting the mechanical interlocking of the materials [ 33 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…This suggests a chemical link between the veneering materials and the Y-TZP substrates, which strengthens the binding. Several other studies suggested that increasing the surface roughness of zirconia by using air abrasion increased ceramic bond strength by promoting the mechanical interlocking of the materials [ 33 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Finger C. and other researchers [34] conducted a study on the effect of sandblasting on surface roughness and residual stresses in zirconium oxide. As part of their research, they showed that the highest values for both parameters are obtained when the sandblasting of the surface with aluminum oxide is performed at an angle of 900.…”
Section: Discussionmentioning
confidence: 99%
“…In an effort to find suitable parameters for sandblasting in this novel lateral screwretained coping method, an experiment was conducted to find the correlation between the surface roughness and the coping retention force. Several parameters in the sandblasting such as the materials, the particle size, the pressure, the distance between the nozzle and the object, the duration, and even the angle may vary [36]. Each variation of the parameter might give different results directly affecting the surface roughness of the abutment which in turn could affect the retention capability of this novel friction-based lateral screw-retained dental crown.…”
Section: Coping Retention Test For Various Surface Roughnessmentioning
confidence: 99%